ANALISIS PERFORMA DAN KEAMANAN SISTEM BACKUP DAN RESTORE PADA PRIVATE CLOUD BERBASIS CASAOS DI LINGKUNGAN VIRTUAL - Lukmanul Hakim; Rama Rara Isano; Yustian Servanda (Jurnal Komputer dan Teknologi, 2026)
Data loss caused by system failures and cyber threats requires a reliable storage protection strategy. This study implements and analyzes an end-to-end encrypted backup system using Duplicati containerized with Docker on a CasaOS-based private cloud deployed within a VirtualBox environment. The research method includes service deployment, mitigation of container network isolation issues, volume mapping misconfigurations, and privilege restrictions, as well as performance measurement using a standard 50 MB backup volume configuration. The experimental results show that the implemented configuration successfully resolved network access limitations and processed backup operations efficiently, achieving an average throughput of 20.22 MB/s for a 1.23 GB dataset. In addition, the restore process was completed successfully after resolving file permission and volume mapping issues. The findings indicate that the integration of CasaOS, Docker, and Duplicati provides a cost-effective, secure, and reliable data protection infrastructure suitable for small- and medium-scale private cloud deployments.